First-Time Mothers’ and Fathers’ Developmental Changes in the Perception of Their Daughters’ and Sons’ Temperament: Its Association With Parents’ Mental Health - Sechi, Cristina; Vismara, Laura; Rollè, Luca; Prino, Laura Elvira; Lucarelli, Loredana (Frontiers in Psychology, 2020)
Objective: Most studies investigating the role of parenting behaviors on the child’s development are directed to mothers. However, recent analyses show that mothers and fathers have a different influence on child’s functioning, specifically her/his temperament. The present study explored the developmental change of parents’ perception of their daughters and sons’ temperament and its association with parental mental health problems. Method: The sample included 188 parents (94 couples) and their at term 94 babies (55.3% boys, 44.7% girls). Assessments by self-reports were conducted at 3 (Time 1) and 12 (Time 2) months after the children’s birth; at Time 1 mothers and fathers independently answered to: The State-Trait Anxiety Inventory (STAI), the Edinburgh Postnatal Depression Scale (EPDS) and the Infant Behavior Questionnaire (IBQ-R;). At Time 2, EPDS, STAI and IBQ-R were again administered to mothers and fathers. Results: In general, mothers and fathers would give similar descriptions of their child’s temperament throughout the first year of life; however, infant temperament showed developmental changes as well as gender differences. Mother and father anxiety and depression symptoms are associated with the infants’ negative affectivity. Also, mothers with high anxiety and depression levels perceive their infants with a minor tendency to approach novelty, to seek environmental stimulation, and to express/experience positive emotions. Conclusions: The results highlight the need to screen for infants' temperament vulnerabilities in the context of maternal and paternal depression in order to protect the child from behavioral, cognitive, and emotional difficulties and to create specific programs aimed at preventing dysfunctional parents-infant relationship.